The Transformation of Import Tax Collection on Consignment Goods through Self-Assessment: An Empirical Study at Soekarno-Hatta International Airport - Agustina, Dian; Abbas, Yulianti (E-Jurnal Akuntansi; Vol 35 No 7 (2025), 2025)
The self-assessment system in the importation of consigned goods is a new policy that shifts the responsibility for reporting and calculating duties and customs values from customs authorities to importers. This study aims to evaluate the implementation of the self-assessment system policy for consigned goods imports using the OECD evaluation criteria, which include relevance, coherence, effectiveness, efficiency, impact, and sustainability. A qualitative approach was employed, with data collected through document analysis and in-depth interviews with policymakers, the Directorate General of Customs and Excise (DGCE), logistics service providers, and importers. The findings of this study indicate that the policy meets the dimensions of coherence, impact, and sustainability, as it has improved importer compliance in reporting import duties and was designed collaboratively to enhance the taxation system and protect domestic production. However, the policy falls short in terms of relevance, effectiveness, and efficiency. From the government's perspective, the policy aligns with national priorities and has the potential to enhance effectiveness and efficiency. However, from the perspective of service users, it introduces additional costs and prolongs the dwelling time in the import process. Strengthening user education, improving information systems, and enhancing cross-sectoral coordination are needed to ensure the optimal and sustainable implementation of the policy. Keywords: Self-Assessment System; Import; Consignment Goods; Policy Evaluation; Customs.